Do migrants get good jobs in Australia? The role of ethnic networks in job search - Stéphane Mahuteau; P. N. (Raja) Junankar (Institute for the Study of Labor (IZA), 2008)
We study the role of ethnic networks in migrants' job search and the quality of jobs they find in the first years of settlement. We find that there are initial downward movements along the occupational ladder, followed by improvements. As a result of restrictions in welfare eligibility since 1997, we study whether this increases the probability that new migrants accept bad jobs quickly and then move onto better jobs over time. Holding employability constant, our results support this view. However, accounting for their higher employability, new migrants seem to fare better up to a year and half after settlement.
urn:nbn:de:101:1-2008052795
Keywords: J61; 330; Migrants; job quality; immigration policy; ethnic networks; Migranten; Arbeitsuche; Soziales Netzwerk; Ethnische Gruppe; Theorie; Australien